Adaptive router promotion and group forming in ad-hoc networks. (16th July 2008) - Sawamura, Takahiro; Tanaka, Kensuke; Atajanov, Merdan; Matsumoto, Noriko, Norihiko Yoshida
In ad-hoc networks, routing is one of the most important issues, and various protocols are proposed. However, as situations and topologies of an ad-hoc network are various and dynamic, it is difficult for a single fixed protocol to perform well for all occasions. Therefore, some dynamic and adaptive mechanism in routing protocols is necessary. In this paper, we propose an adaptive routing system for ad-hoc networks. This system begins in the same manner as a reactive protocol, and when the network situation gets unsuitable for the protocol, the system changes its manner of routing with a router-node, or a pseudo cluster-head in Cluster-based Routing, which emerges autonomously at the place of 'hot spots' in the network. Also, this system provides a protocol to organise a group around each router, or a pseudo cluster, in an autonomous decentralised manner, so that the whole network is organised in a hierarchy of routercentric subnets. This paper presents the principle and design of our system, and some preliminary experiment results.